Salmonella arizona infections in Latinos associated with rattlesnake folk medicine. - Waterman, S H (1990)
In 1987 two Los Angeles County (California) hospitals reported four Latino patients with serious Salmonella arizona (Salmonella subgroup 3) infections who gave a medical history of taking rattlesnake capsules prior to illness. Capsules supplied by the patients or household members grew Salmonella arizona. We reviewed surveillance data for this Salmonella species and conducted a case-control study to determine the magnitude of this public health problem. Eighteen (82 percent) of the 22 Latino cases in 1986 and 1987 who were questioned reported ingesting snake capsules compared to two (8 percent) of 24 matched Latino controls with non-subgroup 3 salmonellosis or shigellosis (matched pair odds ratio = 18.0, CI = 4.2, 76.3). An average of 18 cases per year of Salmonella arizona were reported in the county between 1980 and 1987. In this investigation the majority of S. arizona cases reporting snake capsule ingestion had underlying illnesses such as acquired immunodeficiency syndrome (AIDS), diabetes, arthritis, cancer. The capsules were obtained primarily from Tijuana, Mexico and from Los Angeles, California pharmacies in Latino neighborhoods. Despite publicity and attempts to remove the capsules from sale in California, Salmonella arizona cases associated with snake-capsule ingestion continue to occur.